Variance Analysis with PERT/COST. - Rosen, L. S.; Elikai, Fans; Moriarity, Shane (The Accounting Review, 1982)
Abstract ABSTRACT: This paper presents an extension of PERT/COST which cost accounting instructors can use as the basis for a one- or two-day review of the planning and control cycle. The article stresses performance measurement and responsibility accounting, but the illustrations provided can also be a useful vehicle for a class discussion of such thorny issues as (1) which costs should managers be held responsible for, (2) how should joint costs be allocated, and (3) should joint costs be included in performance reports?